The P2X7 Receptor-Interleukin-1 Liaison - Giuliani, Anna Lisa; Sarti, Alba C.; Falzoni, Simonetta; Di Virgilio, Francesco (Frontiers in Pharmacology, 2017)
Interleukin-1β (IL-1β) plays a central role in stimulation of innate immune system and inflammation and in several chronic inflammatory diseases. These include rare hereditary conditions, e.g. auto-inflammatory syndromes, as well as common pathologies, such as type II diabetes, gout and atherosclerosis. A better understanding of IL-1β synthesis and release is particularly relevant for the design of novel anti-inflammatory drugs. One of the molecules mainly involved in IL-1β maturation is the P2X7 receptor (P2X7R), an ATP-gated ion channel that chiefly acts through the recruitment of the NLRP3 inflammasome-caspase-1 complex. In this review, we will summarize evidence supporting the key role of the P2X7R in IL-1β production, with special emphasis on the mechanism of release, a process that is still a matter of controversy. Four different models have been proposed: i) exocytosis via secretory lysosomes, ii) microvesicles shedding from plasma membrane, iii) release of exosomes, and iv) passive efflux across a leaky plasma membrane during pyroptotic cell death. All these models involve the P2X7R.